ANTI-CRISIS MANAGEMENT OF BANK ACTIVITIES UNDER CONDITIONS OF INTERNAL THREATS - Ryzhonkov , Ilya; Azarenkova , Halyna (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2023)
The development of banking meets crisis situations which due to  social role and the specificity of functions requires a specific method of management as well as measures to prevent crises. The need to develop anti-crisis management occurs at the time of planning banking activities and relates to the specifics of the banking sector.In modern relations the unstable and changing economic situation is prone to constant changes, and as a rule, the inability to quickly adapt to these conditions creates a crisis situation in a bank which turns into a crisis state and becomes a risk for bank existence and requires the immediate implementation of measures for financial recovery .The article considers the concepts of crisis, banking crisis, anti-crisis banking management, provides a primary assessment of anti-crisis measures that are used in domestic banking practice in emergency situations, suggests directions for further work in anti-crisis management to prevent the consequences of a banking crisis at the current stage. It has been found that the banking crisis can be studied as a crisis of a separate banking institution or as a crisis of the entire banking system. The causes of crises have been clarified, the classification of which has been supplemented by a separate group of factors of emergency situations, since they require a more detailed study and the development of appropriate anti-crisis measures to overcome their consequences. It has been determined that anti-crisis management is carried out at different stages and with different goals: in normal conditions of bank functioning - with the aim of preventing a crisis, in crisis conditions - with the aim of overcoming its negative consequences.